Incapacidade funcional em idosos jovens e mais idosos com dor lombar aguda: dados do estudo Back Complaints in the Elders- BACE- Brasil - Alessandra Regina Silva Araujo (2016)
Due to longer life expectancy and decline in the elderly population mortality rate, the elderly and oldest-old population in Brazil is growing. This phenomenon may be accompanied by an increase of musculoskeletal symptoms, including low back pain (LBP), which is usually associated with difficulty in performing activities of daily living (ADL), which can cause disability and affect the overall health status of this population. Objective: To investigate the association between pain intensity (PI) and disability of elderly subjects with acute LBP and assess whether these variables differ depending on the age and marital status. Method: This was an observational study of cross-temporality, conducted with 532 elderly subjects with acute LBP episodes. Pain intensity was evaluated by the Numerical Pain Scale (NPS) and disability by the Late Life Function and Disability Instrument (LLFDI). The normal distribution of data was evaluated using the Kolmogorov-Smirnov test. The association between PI and disability analysis was conducted via Spearman correlation test, and the Anova two way and Kruskal Wallis testswere used to assess differences between groups. Results: Correlation in relation to pain analysis showed minimal association (rho <0.20) withdisability. Considering the age and marital status, pain and disabilitycorrelated inversely, furthermore older seniors and the elderly who lived with a partner showed lower frequency of activities and the elderly living alone reported feeling more pain. Conclusion: The results indicate that elderly disability does not depend on perceived pain intensity. However, disability is negatively influenced in the oldest old living with a partner. About the intensity of acute PI, it is clear that living with a partner can be a protective factor for the perception and exacerbation of pain intensity.